A state-of-the-art techno-economic review of distributed and embedded energy storage for energy systems. (15th August 2021) - McIlwaine, Neil; Foley, Aoife M.; Morrow, D. John; Al Kez, Dlzar; Zhang, Chongyu; Lu, Xi; Best, Robert J.
Abstract: Renewable energy is projected to play an important role in reducing greenhouse gas emissions and in realising the climate change goals. Large scale development of variable renewable energy, which is regarded as non-dispatchable, requires additional power system quality services such as voltage regulation, frequency regulation and inertial response. Energy storage provides an important means to supply these services but there are many uncertainties in terms of technology, market readiness, economics, and regulatory requirements. The aim of this study is to undertake a global state-of-the-art review of the techno-economic and regulatory status of energy storage and power quality services at the distribution level. The review will establish the global trends in electricity markets that have seen high levels of renewable energy penetration. The results of the investigation indicate that further research is required to qualify, quantify, and value the installation of mass energy storage particularly at the distribution level. Highlights: Grids to operate at system non-synchronous penetration in excess of 75%. Growth in renewables and less synchronous generation causes grid system challenges. Battery energy storage at distribution level can provide grid system services. Embedded battery storage installed behind the meter at distribution level.